Effects of a Spleen Peptide Preparation as Supportive Therapy in Inoperable Head and Neck Cancer Patients - Borghardt, Jürgen; Rosien, Bernd; Görtelmeyer, Roman; Lindemann, Svenja; Hartleb, Martin; Klingmüller, Martin (Arzneimittelforschung, 2000)
Patients with inoperable head and neck cancer were treated with a spleen peptide preparation (Poly-erga®) in a phase III randomized, placebo-controlled double-blind study during chemotherapy (cispla-tin/carboplatin, 5-fluorouracil) to investigate further the efficacy of this peptide preparation as supportive treatment under chemotherapy. Immunological changes as well as quality of life aspects were examined. Forty patients were included in this study.The peptide preparation had a significant stabilizing effect on the peripheral blood lymphocyte status during chemotherapy cycles (Student t-test, p = 0.05) and tended to stabilize the shift of granulocyte count (Student t-test, p = 0.18). In addition, the group receiving the verum showed a remarkable stabilization of body weight (Mann-Whitney U-test, p = 0.17) during chemotherapy treatment and the generally observed increase of fatigue-inertia during the chemotherapy cycles was significantly reduced (Student t-test, p = 0.01).
Keywords: Head and neck cancer, chemotherapy, supportive therapy with spleen peptides; Polyerga®, clinical studies, supportive cancer therapy; Spleen peptides